2014
DOI: 10.1007/s10071-014-0730-7
|View full text |Cite
|
Sign up to set email alerts
|

Gambling primates: reactions to a modified Iowa Gambling Task in humans, chimpanzees and capuchin monkeys

Abstract: Humans will, at times, act against their own economic self-interest, for example, in gambling situations. To explore the evolutionary roots of this behavior, we modified a traditional human gambling task, the Iowa Gambling Task (IGT), for use with chimpanzees, capuchin monkeys and humans. We expanded the traditional task to include two additional payoff structures to fully elucidate the ways in which these primate species respond to differing reward distributions versus overall quantities of rewards, a compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…In other cases, the payoff contingencies may be adjusted across trials to test how animals modulate their choices when expected values shift. In many studies, animals first gain experience with reward contingencies in a learning phase to then examine stabilized choice preferences in a test phase [50][51][52][53][54][55][56][57], whereas other studies focus on how animals learn about the value and variance of different outcomes [58,59]. This basic kind of paradigm has been used with multiple primate species, including chimpanzees (Pan troglodytes) [50,58,59], bonobos (Pan paniscus) [50], gorilla (Gorilla gorilla) [59], rhesus macaques (Macaca mulatta) [51][52][53][54][55], Japanese macaques (Macaca fuscata) [59], capuchin monkeys (Sapajus apella) [56,58] and several lemur species (Lemur catta, Eulemur mongoz, Varecia rubra) [57], in some cases with comparisons with humans [58,60].…”
Section: Measuring Animal Decision-makingmentioning
confidence: 99%
“…In other cases, the payoff contingencies may be adjusted across trials to test how animals modulate their choices when expected values shift. In many studies, animals first gain experience with reward contingencies in a learning phase to then examine stabilized choice preferences in a test phase [50][51][52][53][54][55][56][57], whereas other studies focus on how animals learn about the value and variance of different outcomes [58,59]. This basic kind of paradigm has been used with multiple primate species, including chimpanzees (Pan troglodytes) [50,58,59], bonobos (Pan paniscus) [50], gorilla (Gorilla gorilla) [59], rhesus macaques (Macaca mulatta) [51][52][53][54][55], Japanese macaques (Macaca fuscata) [59], capuchin monkeys (Sapajus apella) [56,58] and several lemur species (Lemur catta, Eulemur mongoz, Varecia rubra) [57], in some cases with comparisons with humans [58,60].…”
Section: Measuring Animal Decision-makingmentioning
confidence: 99%
“…4). To do this, a cumulative performance index was calculated by taking the number of correct choices minus the number of incorrect choices across trial blocks (the total number of trials divided into four blocks; Glicksohn et al 2007;Proctor et al 2014). In order to classify learning, the cumulative performance index had to result in a monotonic function (Fig.…”
Section: Transfer Testmentioning
confidence: 99%
“…Animal subjects are expected to learn about relative outcome frequencies from experience, but previous studies on risk do not give clear evidence of whether or how this occurs (Bateson & Kacelnik, 1997;Brito-e-Abreu & Kacelnik, 1999;De Petrillo et al, 2015;Hayden et al, 2008;Heilbronner & Hayden, 2013, Proctor et al, 2014. For example, Yamada et al (2013) showed that, although macaques exhibited a strategy in the early stages of testing that was interpreted as risk seeking, they shifted to neutral or slightly risk-averse attitudes after exposure to the tests.…”
Section: Introductionmentioning
confidence: 99%